Results of medical and biological researches of Ukrainian scientists at Elbrus - Білошицький, П.В.; Ключко, О.М.; Онопчук, Ю.І. (Proceedings of National Aviation University (archive), 2022)
Brief results of medical and biological researches of Ukrainian scientists at Elbrus mountain conditions during last decades is given. Main attention is paid to the directions linked with the development of aviation and cosmonautics.